Cajal's interactions with Sherrington and the Croonian Lecture - De Carlos, JA; Molnar, Z (Wiley, 2019)
Sherrington was a major proponent of the neuron doctrine and he was inspired by Santiago Ramón y Cajal's theory of dynamic polarization of nerve cells (Ley de la polarización dinámica de la célula nerviosa). Sherrington coined the term "synapse" to name the Cajal description of interneuronal contact and he gave the term, for functional nerve endings, as "Boutons terminaux," still used today. These two giants of neuroscience met only once, but they had a life-long friendship. It was Sherrington who wrote Cajal's Obituary for the Royal Society. We review here some of the scientific exchanges between Cajal and Sherrington, with particular attention to 1894, when the two neuroscientist met in London during Cajal's visit to deliver the Croonian Lecture to the Royal Society. We shall examine not only the scientific exchanges but also their friendship, which was immediate and strong.